2022
DOI: 10.1002/jvc2.93
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and psoriasis: A review based on statements of the telemedicine working group of the International Psoriasis Council

Abstract: During the past few decades, classical in‐person communication has been enriched by opportunities for telemedicine. We are in a learning healthcare environment that takes advantage of the opportunities of telemedicine and in‐person consultations, reconciling the individuality of the patient and his/her psoriasis. A working group of experts in telemedicine was installed by the International Psoriasis Council (IPC) to formulate the opportunities and limitations of telemedicine in the diagnosis and treatment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…They showed that diagnoses of patients with PsO via TD were detected well comparable with FTF examination. A number of guidelines developed by dermatologists also provide some recommendations regarding the use of TD for PsO [18,19]. As a result, while TD has been reported to be a useful technique for the diagnosis of PsO, FTF examinations are still required in patients who may require skin biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that diagnoses of patients with PsO via TD were detected well comparable with FTF examination. A number of guidelines developed by dermatologists also provide some recommendations regarding the use of TD for PsO [18,19]. As a result, while TD has been reported to be a useful technique for the diagnosis of PsO, FTF examinations are still required in patients who may require skin biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, telemedicine remains absent from existing (European) guidelines for psoriasis or atopic dermatitis ( 10 , 11 ). However, it gains more attention, and the International Psoriasis Council formulated a call to action, based on several statements concerning telemedicine ( 12 ). The objective of this systematic review is to quantitatively evaluate the efficacy and safety outcomes of telemedicine compared with in-person care for chronic inflammatory skin diseases.…”
mentioning
confidence: 99%